1990
DOI: 10.1620/tjem.161.329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hand and spatial conditions on visual line bisection.

Abstract: This study examined the effects of hand and spatial conditions on a visual line bisection task with normal right-handers and proposed a normal range of deviation for this task in middle and advanced age. Twentyfour normal dextrals in their fifties and sixties performed a visual line bisection task using either the left or right hand under three spatial conditions : at the midline and in the left and right hemispaces. Our results revealed that performance was significantly affected by the hand used but not spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 9 publications
2
34
1
Order By: Relevance
“…Most studies have used mixed sex subject groups [31,48,50,60,79,95,113,120] or failed to report the sex of subjects [4,6,9,11,40,57,95,103,111]. The majority of studies examining the in¯uence of sex report non-signi®cant eects [16,19,30,42,73,86,92,110,115]. However, Roig and Cicero [105] found that males erred more to the 2 While various response criteria have been used to measure bisection performance, this review uses mean signed deviation from veridical center as a response measure since it captures both the direction and amplitude of bisection errors.…”
Section: Sexmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have used mixed sex subject groups [31,48,50,60,79,95,113,120] or failed to report the sex of subjects [4,6,9,11,40,57,95,103,111]. The majority of studies examining the in¯uence of sex report non-signi®cant eects [16,19,30,42,73,86,92,110,115]. However, Roig and Cicero [105] found that males erred more to the 2 While various response criteria have been used to measure bisection performance, this review uses mean signed deviation from veridical center as a response measure since it captures both the direction and amplitude of bisection errors.…”
Section: Sexmentioning
confidence: 99%
“…Most studies have limited testing to dextral subjects [19,23,30,31,38,41,42,48,50,60,61,62,79,84,87,91,94,97,111,115,120,126]. Many, however, fail to disclose subject handedness [4,6,11,22,40,57,98,103,113,118].…”
Section: Handedness/lateralitymentioning
confidence: 99%
See 1 more Smart Citation
“…Line bisection is a task that may be affected by different factors [13][14][15][16][17][18][19][20][21][22][23][24][66][67][68][69][70][71][72][73]. However, the factors related to the stimulus were comparable between the studies that found a leftward and those that found a rightward bisection bias.…”
Section: Rightward Bisection Bias Left Hemineglectmentioning
confidence: 99%
“…Further, when normal subjects are asked to bisect radial or vertical lines, they usually deviate away from, or above the true midpoint, respectively [11,12]. The magnitude and the direction of bisection errors may be influenced by stimulus or task factors, such as line length [13,14] and location [15][16][17], the hand used [18,19], the presence of contextual stimuli [20][21][22][23], the directional scanning [24].…”
Section: Introductionmentioning
confidence: 99%